A Behavioral Genetic Analysis of the Cooccurrence Between Psychopathic Personality Traits and Criminal Behavior. (February 2019) - Lewis, Richard H.; Connolly, Eric J.; Boisvert, Danielle L.; Boutwell, Brian B.
A developed line of research has found that psychopathic personality traits and criminal behavior are correlated with one another. Although there is little question about the association between psychopathic personality traits and criminal behavior, what remains less clear is whether psychopathic traits exert a direct effect on criminal behavior. An alternative possibility is that previously unmeasured genetic and shared environmental factors account for much of the association between the two. Understanding the extent to which genetic and environmental factors influence the covariance between psychopathic personality traits and criminal behavior can further our understanding of individual differences in propensity to engage in antisocial behavior. The current study analyzes 872 twins (MZ twins = 352, DZ twins = 520) from the National Longitudinal Study of Adolescent to Adult Health (Add Health) to examine the magnitude of genetic and environmental effects on the covariation between psychopathic personality and criminal behavior. Results from bivariate behavioral genetic analyses revealed that the correlation between psychopathic personality traits and criminal behavior was accounted for by common additive genetic (58%) and nonshared environmental (42%) influences. Fixed-effect linear regression models, however, suggested that psychopathic personality traits were not significantly associated with criminal behavior once common genetic and environmental influences were taken into account.